MYD88, CARD11, and CD79B Oncogenic Mutations are Rare Events in the Indian Cohort of De Novo Nodal Diffuse Large B-Cell Lymphoma. Issue 4 (April 2019) - Aggarwal, Vaishali; Das, Ashim; Bal, Amanjit; Srinivasan, Radhika; Das, Reena; Prakash, Gaurav; Malhotra, Pankaj; Varma, Subhash
Abstract : Diffuse large B-cell lymphoma (DLBCL) has a heterogenous biological behavior, and the western literature has reported activating oncogenic mutations in myeloid differentiation primary response gene 88 ( MYD88 ), in conjunction with B-cell receptor signaling pathway genes, CARD11 and CD79B as the driving force for activating the NF-κB pathway implicated in the pathogenesis of DLBCL. The mutation profile of MYD88 genes was evaluated by Sanger sequencing in a cohort of 97 patients [DLBCL (N=55), non-DLBCL lymphomas (N=30), reactive lymphadenopathy (N=10), and 2 cases of lymphoplasmacytic lymphoma (positive control)]. The mutation profile of CARD11 and CD79B were evaluated in 70 patients [DLBCL (N=30), non-DLBCL lymphomas (N=30), and reactive lymphadenopathy (N=10). MYD88 and NF-κB mRNA expression was also evaluated by quantitative reverse transcriptase polymerase chain reaction. These 55 cases of DLBCL were classified into germinal center B-cell and activated B-cell phenotypes using Hans algorithm, of which 58% were of activated B-cell phenotype and 42% were of germinal center B-cell phenotype. MYD88 mutation was seen in 3.6% (2/55) of DLBCL cases, indicating a lower frequency in Indian de novo DLBCL. The mutations detected were novel 33 bp deletion g.7735_7767del (p.V294_S305del) and a splice-acceptor site mutation in exon 5 of MYD88, different from the reported hotspot mutation MYD88 L265P. CARD11 and CD79B mutations were absent in DLBCL and other lymphoma subtypes. MYD88 transcript expression did not correlate with mutational status. NF-κB showed significant overexpression in MYD88 mutation–negative ( P =0.004) DLBCL cases indicating that its regulation is independent of MYD88, CARD11, and CD79B mutations, implying the existence of alternative activating pathways. In silico analysis of 2 novel mutations predicted disruptive structural changes in the B-B loop of the translated protein whose biological significance needs further evaluation. Abstract : Supplemental Digital Content is available in the text.